Organic Production as a Key for Sustainable Development in Wine Industry in the Czech Republic - Formánková, Sylvie; Chládková, Helena; Beránková, Anita (Táplálkozásmarketing, 2016)
The paper describes the environment sector of organic winery in the Czech Republic and finds opportunities for Czech winegrowers to sustain the industry and contribute to its future development. Organic viticulture has changed dramatically. Organically farmed vineyards formed 4.9% share of the total area of vineyards in the Czech Republic in 2011 and 6.1% in 2012. Czech organic wines have much to offer to consumers. They have received many prestigious awards at international competitions; however the foreknowledge of customers about such wines is very low as these are drunk mostly by regular consumers. That is why a change should be made. The popularity of organic wine is expected to grow mainly in the foreign markets. Although the Czech organic wines have already found their consumers, the need for additional marketing activities that will result in expansion of its portfolio of consumers, are required.JEL codes: M1, M11, M 13, M14